2022
DOI: 10.1039/d2dt00983h
|View full text |Cite
|
Sign up to set email alerts
|

Visible and near-infrared photoluminescence of a supramolecular complex constructed from a cycloparaphenylene nanoring and an erbium metallofullerene

Abstract: Erbium metallofullerenes exhibit near-infrared photoluminescence from the Er3+ ion, which has potential application in telecommunication, optical devices and bioscience. In this manuscript, we construct a supramolecular complex of metallofullerene Er3N@C80...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…As hosts for numerous guest molecules such as smaller rings, [35][36][37][38] fullerenes, [38][39][40][41][42][43] fullerene dumbbells, [24,[44][45][46][47] endohedral metallo fullerenes, [36,[48][49][50][51][52] larger PAHs [53][54][55] and organic cations, [56] CPPs represent a tremendously important contribution to the world of noncovalent inclusion complexes. Bonding results from concave/convex π-π, CH-π and/or charge-π interactions between host and guest.…”
Section: Introductionmentioning
confidence: 99%
“…As hosts for numerous guest molecules such as smaller rings, [35][36][37][38] fullerenes, [38][39][40][41][42][43] fullerene dumbbells, [24,[44][45][46][47] endohedral metallo fullerenes, [36,[48][49][50][51][52] larger PAHs [53][54][55] and organic cations, [56] CPPs represent a tremendously important contribution to the world of noncovalent inclusion complexes. Bonding results from concave/convex π-π, CH-π and/or charge-π interactions between host and guest.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Besides, a special supramolecular complex with both visible and near-infrared photoluminescence was also constructed by inserting the Er 3 N@C 80 into the cavity of [12]CPP. [35] Shortly before, an extensive overview of supramolecular purification and regioselective functionalization of fullerenes and metallofullerenes based on diverse host molecules has been published by Xavi Ribas's group. [36] For metallofullerene-based supramolecular complexes, the orientation of metallofullerene guest is interesting.…”
Section: Supramolecular Assemblymentioning
confidence: 99%
“…Recently, we also found that in DyY 2 N@C 80 ⊂[12]CPP the host‐guest interactions can influence the photoluminescence of fullerene cage [34] . Besides, a special supramolecular complex with both visible and near‐infrared photoluminescence was also constructed by inserting the Er 3 N@C 80 into the cavity of [12]CPP [35] . Shortly before, an extensive overview of supramolecular purification and regioselective functionalization of fullerenes and metallofullerenes based on diverse host molecules has been published by Xavi Ribas's group [36] …”
Section: Supramolecular Assemblymentioning
confidence: 99%
“…Cycloparaphenylenes (CPPs) also represent very suitable host molecules for fullerenes and fullerene derivatives. Since their first synthesis by Jasti et al in 2008, 18 host-guest complexes between CPPs and pristine [19][20][21][22][23][24] and endohedral metallofullerenes [25][26][27][28][29][30][31] have been extensively studied. In 2015, Itami et al reported the first preparation and characterization of a complex between [10]CPP and Li + @C 60 .…”
Section: Introductionmentioning
confidence: 99%